Case report: Open water swimming as a possible treatment for asthma - Greenfield, Kirsty; Verling, William; Larcombe, Thomas; Connett, Gary James (Frontiers in Medicine, 2023)
Asthma is a complex medical problem for which currently available treatment can be incompletely effective. This case report describes a 49 year old woman who had suffered from asthma since her teenage years that resolved after she took up regular open water swimming. After sharing this case report with an international open water swimming community on social media, over one hundred people with asthma commented that their symptoms had also improved after taking up this activity. The mechanism whereby open water swimming might alleviate asthma has not been established. Possibilities include benefits to mental health, anti-inflammatory effects, being more fit, improved immune function and suppression of the broncho constrictive component of the diving reflex. Further research might usefully confirm or refute these clinical observations.